Exome sequencing reveals IFT172 variants in patients with non-syndromic cholestatic liver disease - Neřoldová, Magdaléna; Ciara, Elżbieta; Slatinská, Janka; Fraňková, Soňa; Lišková, Petra; Kotalová, Radana; Globinovská, Janka; Šafaříková, Markéta; Pfeiferová, Lucie; Zůnová, Hana; Mrázová, Lenka; Stránecký, Viktor; et al. (PLoS One, 2023)
BACKGROUND AND AIM: Gene defects contribute to the aetiology of intrahepatic cholestasis. We aimed to explore the outcome of whole-exome sequencing (WES) in a cohort of 51 patients with this diagnosis. PATIENTS AND METHODS: Both paediatric (n = 33) and adult (n = 18) patients with cholestatic liver disease of unknown aetiology were eligible. WES was used for reassessment of 34 patients (23 children) without diagnostic genotypes in ABCB11, ATP8B1, ABCB4 or JAG1 demonstrable by previous Sanger sequencing, and for primary assessment of additional 17 patients (10 children). Nasopharyngeal swab mRNA was analysed to address variant pathogenicity in two families. RESULTS: WES revealed biallelic variation in 3 ciliopathy genes (PKHD1, TMEM67 and IFT172) in 4 clinically unrelated index subjects (3 children and 1 adult), heterozygosity for a known variant in PPOX in one adult index subject, and homozygosity for an unreported splice-site variation in F11R in one child. Whereas phenotypes of the index patients with mutated PKHD1, TMEM67, and PPOX corresponded with those elsewhere reported, how F11R variation underlies liver disease remains unclear. Two unrelated patients harboured different novel biallelic variants in IFT172, a gene implicated in short-rib thoracic dysplasia 10 and Bardet-Biedl syndrome 20. One patient, a homozygote for IFT172 rs780205001 c.167A>C p.(Lys56Thr) born to first cousins, had liver disease, interpreted on biopsy aged 4y as glycogen storage disease, followed by adult-onset nephronophthisis at 25y. The other, a compound heterozygote for novel frameshift variant IFT172 NM_015662.3 c.2070del p.(Met690Ilefs*11) and 2 syntenic missense variants IFT172 rs776310391 c.157T>A p.(Phe53Ile) and rs746462745 c.164C>G p.(Thr55Ser), had a severe 8mo cholestatic episode in early infancy, with persisting hyperbilirubinemia and fibrosis on imaging studies at 17y. No patient had skeletal malformations. CONCLUSION: Our findings suggest association of IFT172 variants with non-syndromic cholestatic liver disease.
Keywords: adaptorové proteiny signální transdukční; Cholestasis, Intrahepatic; protoporfyrinogenoxidasa; mitochondriální proteiny; lidé; mutace; Adaptor Proteins, Signal Transducing; cholestáza; Cholestasis; Genotype; genotyp; cytoskeletální proteiny; Flavoproteins; Mutation; Humans; Cytoskeletal Proteins; Protoporphyrinogen Oxidase; sekvenování exomu; intrahepatální cholestáza; Mitochondrial Proteins; Exome Sequencing; flavoproteiny